2018
DOI: 10.1007/s00436-018-5818-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic uniqueness of Cryptosporidium parvum from dairy calves in Colombia

Abstract: Fecal specimens from 432 pre-weaned calves younger than 35 days were collected over a 2-year period (2010-2012) from 74 dairy cattle farms in the central area of Colombia. These samples were microscopically examined for the presence of Cryptosporidium oocysts, and positive specimens were selected for molecular examination. Microscopy revealed that 115 calves (26.6%) from 44 farms (59.5%) tested positive. Oocyst shedding was recorded in calves aged 3-day-old onwards, although the infection rate peaked at 8-14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 60 publications
2
23
2
4
Order By: Relevance
“…At least one C. parvum-positive calf was detected in 89% of the herds studied. Highly variable herd prevalence ranging from 50.5 to 96% have been reported (Hamnes et al 2006;Brook et al 2008;Trotz-Williams et al 2008;Silverlås et al 2009;Tiranti et al 2011;Smith et al 2014;Al Mawly et al 2015;Delafosse et al 2015;Garro et al 2016;Avendaño et al 2018). Similar to the considerable differences of overall prevalence that have been reported, corresponding dissimilarities in herd prevalence may likewise be attributed to the different sensitivities of applied diagnostic test.…”
Section: Dairy Herdmentioning
confidence: 69%
See 1 more Smart Citation
“…At least one C. parvum-positive calf was detected in 89% of the herds studied. Highly variable herd prevalence ranging from 50.5 to 96% have been reported (Hamnes et al 2006;Brook et al 2008;Trotz-Williams et al 2008;Silverlås et al 2009;Tiranti et al 2011;Smith et al 2014;Al Mawly et al 2015;Delafosse et al 2015;Garro et al 2016;Avendaño et al 2018). Similar to the considerable differences of overall prevalence that have been reported, corresponding dissimilarities in herd prevalence may likewise be attributed to the different sensitivities of applied diagnostic test.…”
Section: Dairy Herdmentioning
confidence: 69%
“…reported that cryptosporidiosis risk is higher in calves younger than 30 days old (Tiranti et al 2011;Smith et al 2014;Delafosse et al 2015;Avendaño et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…A wide range of subtypes belonging to a single gp60 allelic family have been reported in Brazil (IIaA14G2R1, IIaA14G2R2, IIaA15G2R1, IIaA16G3R2, IIaA17G2R1, IIaA18G1R1, IIaA18G2R2, IIaA19G2R1, IIaA19G2R2, IIaA20G1R1; IIaA20G2R1, IIaA20G2R2) (Meireles et al, 2011;Paz e Silva et al, 2013;do Couto et al, 2014;Heckler et al, 2015;Toledo et al, 2017), Argentina (IIaA16G1R1, IIaA17G1R1, IIaA18G1R1, IIaA19G1R1, IIaA20G1R1, IIaA21G1R1, IIaA22G1R1, IIaA23G1R1) (Tomazic et al, 2013;Del Coco et al, 2014) and Chile (IIaA15G4R1, IIaA16G4R1, IIaA17G4R1) (Mercado et al, 2015). The fact that many of these subtypes were novel allelic variants or were not shared among different countries has been related to the geographic isolation of the protozoan in cattle farms (Avendaño et al, 2018). The latter authors conducted the first large study of Cryptosporidium species and subtypes in Colombia, which revealed the distinct identity of C. parvum circulating in calves.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of 70 C. parvum isolates from a previous study was used in this molecular analysis (Avendaño et al, 2018). These isolates were collected between 2010 and 2012 from naturally infected diarrhoeic (n: 25) and non-diarrhoeic (n: 45) calves younger than 35 days.…”
Section: Cryptosporidium Isolatesmentioning
confidence: 99%
See 1 more Smart Citation